2016
DOI: 10.1061/(asce)ir.1943-4774.0000932
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Furrow Irrigation Sediment Loss Using an Artificial Neural Network

Abstract: The area irrigated by furrow irrigation in the United States has been steadily decreasing but still represents about 20% of the total irrigated area in the United States. Furrow irrigation sediment loss is a major water quality issue, and a method for estimating sediment loss is needed to quantify the environmental effects and estimate effectiveness and economic value of conservation practices. Artificial neural network (NN) modeling was applied to furrow irrigation to predict sediment loss as a function of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The collective data set included nine common hydraulic and field condition variables: freshly cultivated or previously eroded by prior irrigation; compacted by wheel traffic or uncompacted; irrigation duration (T, h); furrow length (L, m); furrow inflow rate (Q, L min -1 ); furrow slope (S, %); soil sand and clay fractions (%); and furrow sediment loss (SL, kg). Additional details on the data sources are provided by King et al (2016).…”
Section: Databasementioning
confidence: 99%
See 1 more Smart Citation
“…The collective data set included nine common hydraulic and field condition variables: freshly cultivated or previously eroded by prior irrigation; compacted by wheel traffic or uncompacted; irrigation duration (T, h); furrow length (L, m); furrow inflow rate (Q, L min -1 ); furrow slope (S, %); soil sand and clay fractions (%); and furrow sediment loss (SL, kg). Additional details on the data sources are provided by King et al (2016).…”
Section: Databasementioning
confidence: 99%
“…Linear regression and feedforward neural networks (FFNN) are examples of supervised learning where model parameters are adjusted to minimize the sum of square errors between model predications and a measured value. King et al (2016) used a feed-forward artificial neural network (FFNN) to model furrow sediment loss resulting in an R 2 = 0.71 between predicted and measured sediment loss. The desire to maximize prediction performance resulted in an over-trained model where the model learned the data set rather than underlying physical relationships representing the furrow sediment loss process.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of surface soil reduces soil fertility and ultimately prevents agricultural cultivation. Factors affecting soil erosion in furrow‐irrigated land include field slope, soil type (soil texture and structure), field dimensions, inflow rate, crop characteristics and the duration of the irrigation event (Fernández‐Gómez et al, 2004; King et al, 2016; Truman & Nuti, 2009; Westermann et al, 2001). In open‐end furrow irrigation, a large part of the inflow water is released from the end of the furrow as runoff.…”
Section: Introductionmentioning
confidence: 99%
“…For example, King et al . () utilized ANNs for estimation of sediment loss in furrow irrigation based on hydraulic and soil conditions. They demonstrated that the performance of ANNs was better than the efficiency of previously employed sediment loss prediction approaches including physical and empirical models.…”
Section: Introductionmentioning
confidence: 99%
“…The applications of ANNs in various fields of water resources are promising and description of all related references is beyond the scope of this study and only some related works are presented here. For example, King et al (2015) utilized ANNs for estimation of sediment loss in furrow irrigation based on hydraulic and soil conditions. They demonstrated that the performance of ANNs was better than the efficiency of previously employed sediment loss prediction approaches including physical and empirical models.…”
Section: Introductionmentioning
confidence: 99%